Featured Cover. (13th March 2023) - Reindl, Robert; Neuner, Johann; Schletterer, Martin
Abstract : The cover image is based on the Research Article Increased hydropower production and hydropeaking mitigation along the Upper Inn River (Tyrol, Austria) with a combination of buffer reservoirs, diversion hydropower plants and retention basins by Robert Reindl et al., https://doi.org/10.1002/rra.4052 .